Hubungan Antara Faktor Risiko pada Ibu Hamil dengan Kejadian Stunting di Wilayah Kerja Puskesmas Mandastana, Kabupaten Barito Kuala - Dhewi, Siska (Jurnal Kesehatan Indonesia, 2023)
Data from the Asian Development Bank (ADB) in November 2021 showed that Indonesia was in the second highest position in Southeast Asia for the prevalence of children that has stunting occurance under five years old. The Permata Bunda program is one of the priority programs of the Batola Regency Government in the form of providing food to children under five who have malnutrition, good nutrition and pregnant women with chronic energy deficiency, as well as pregnant women and toddlers from underprivileged families, restoring the children under five and pregnant women’s nutritional status. The study design used in this study is a case control design, a quantitative analytic study, which is to determine the correlation between age, parity, Chronic Energy Deficiency (CED), anemia and maternal weight gain with the incidencef stunting in children under five. There is a correlation between maternal parity, the incidence of SEZ and the occurance of anemia with the occurance of stunting toddlers and there is no correlation between age and maternal weight gain during phase of pregnancy and the incidence of stunting in children under five. The health workers in Puskesmas are suggested to prioritize the risk of CED and anemia in pregnant women to prevent the problem of stunting in children.